The Effects of Te2− and I− Substitutions on the Electronic Structures, Thermoelectric Performance, and Hardness in Melt‐Quenched Highly Dense Cu2‐xSe. (5th February 2015) - Zhao, Lanling; Wang, Xiaolin; Yun, Frank F.; Wang, Jiyang; Cheng, Zhenxiang; Dou, Shixue; Wang, Jun; Snyder, G. Jeffrey
<x xml:space="preserve">Abstract</x> A systematic study has been carried out on the electronic band structure and density of states, crystal structures, thermoelectric properties, and hardness of the Cu2‐xSe system with and without Te2− or I− substitutions for Se2−. Density functional theory calculations indicate that stoichiometric Cu2Se is a zero‐gap material, and copper‐deficient Cu1.875Se is a p‐type conductor. Te2– substitution increases the total density of states at the Fermi level, whereas, the I− substitution leads to the reduction of the total and partial density of states for both Se and Cu. Highly dense undoped, Te‐doped, and I‐doped Cu2‐xSe bulks have been fabricated by a melt‐quenching method which only takes a few minutes. Rietveld refinements of the X‐ray diffraction patterns reveal that the unit cells are expanded after doping. All the fabricated bulks are p‐type conductors in accordance with band structure calculations, and they all have figure of merit, zT, values over or close to 1.0 at T = 973 K, except for the Cu2‐xTe0.16Se0.84. Furthermore, the hardness is distinctly improved by the doping approach, with a maximum value of ca. 0.66 GPa for the Cu2‐xTe0.16Se0.84, which is higher than those of polycrystalline Bi2Te3 and PbTe bulks.